OPTIMALISASI PEMANFAATAN LIMBAH AGROINDUSTRI MELALUI SUPLEMENTASI MINERAL Ca dan Mg ORGANIK TERHADAP KCBK DAN KCBO RANSUM KAMBING - Vera Septiani; Muhatarudin -; Yusuf Widodo (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
This research aimed to: 1) know the effect of the usage of the supplement of Ca and Mg organic in ration to the digestibility of dry matter and organic matter on goats; 2) know the best effect of the usage of the supplement of Ca and Mg organic in ration to the digestibility of dry matter and organic matter on goats.  This research was held in September until October 2012, located in the pen of Department of Animal Husbandry, Faculty of Agriculture, University of Lampung.  The analysis of feedstuff and feces wes held in Laboratory of Animal’s Feedstuff, Department of Animal Husbandry.  This research used Randomized Block Design with three treatments and three replications. The body weights are as the replications.  The treatments used are R0 = Bassal Ration, R1 = Bassal Ration + Organic Mineral (0,50% Ca, 0,04% Mg), R2 = Bassal Ration + Organic Mineral (1,00% Ca, 0,08% Mg).  The data obtained was statistic tested to know the treatments effect to the variables observed by Variance Analysis.  Then, it was continued by Least Significant Different (LSD) on significant level 5% and or 1%.  The result of the research showes that; the supplement of Ca and Mg Organic  Mineral is non significant (P>0,05) to the digestibility of dry matter and organic matter.   Keywords : agroindustry waste, Ca and Mg organic, the digestibility, goats.